Relations in the Alluvial Zone: Place and Indigenous Knowledges in Michael Marker’s Scholarship - McGregor, Heather E.; Higgins, Marc (Journal of Contemporary Issues in Education, 2023)
Through more than 20 years of scholarship, Michael Marker brings our attention, again andagain, and more deeply, to the sentient, relational, spiritual, and political dimensions of place.This analytic review of his body of work illuminates Marker’s teachings on place, specifically, ineducation, history, and Indigenous knowledges. It is an effort to both crystalize and mobilize hisconceptualization to inform future work by others. Place, Marker teaches us, functions as anagent in the transmission of knowledge and in the course of events over time (sometimes referred to as history). Place is also centered in Marker’s research as an analytic tool. He incisively points out the consequences of neglecting the aforementioned dimensions of place from Indigenous perspectives and for Indigenous communities, as well as their relations in teaching, learning, and research contexts. In his later work, Marker (2019a) introduces the metaphor of alluvial zones to characterize the co-presence of Indigenous and Western epistemologies and ontologies in the university setting. Marker (2019a) traces the metaphor, which will be further detailed below, by referring to university spaces as a “transforming river delta,” a place that has the potential to yield the “most fertile soils in the world,” wherein sediments (knowledges) unite in one sense, but remain distinct in another (pp. 502-503). We work with Marker’s metaphor of the university as an alluvial zone to consider conceptualization and enactment of place as emblematic of Western and Indigenous knowledges coming together to both combine and not combine in ways that matter. In our resulting review of his work we found six themes on which we elaborate: recognizing local ancestors; placing knowledges; sustaining land relationships; engaging responsibilities; nurturing spirits; and confronting place refusals.